Description of the Government Depot at Kodibag - Kaikini, D. S. (Indian Forester, 1937)
The Government timber depot at Kodibag is the largest on the coast and was established in the sixties and stocks some of the finest teak timber from three Kanara Forest divisions. supplying the needs of Kathiawar and Bombay. Elephants play an important part in the operations. The Kodhag Bundarls important for the traffic in timber as well as fuel from the coupes of the Fuel Reserves. Two years ago the traffic was so great that the creek was full of country craft and presented a picturesque appearance. This traffic has lately dl-nlnlshed as demand for fuel in Bombay has considerably fallen. The annual export of timber and fuel from Kodibag aggregates Rs. 2,30,000 in value.